Minimising students' communication apprehension: the application of groupwork learning strategy in English classrooms - Sahar, Rafidah; Abdullah, Nur Nabilah; Engku Ibrahim, Engku Haliza (IIUM Press, 2011)
This study investigated the effectiveness of groupwork as a learning strategy during class lectures and discussions to promote active participation, boost self-confidence and attain higher course achievement among pre-university students studying in an intensive English course. Students were exposed to a variety of strategies that incorporated the essesnce of groupwork learning to reduce their anxiety in oral communication. Students' communication apprehension (CA) scores at the beginning and at the end of the course were compared. The results illustrated that in general students' level of anxiety was reduced from a very high level of CA to a modestly high level of CA when groupwork was used as a learning strategy, which in turn, encouraged them to actively partake in communicative activities, thus enhancing their learning.